Verbal fluency in Alzheimer’s disease and mild cognitive impairment in individuals with low educational level and its relationship with reading and writing habits - Tessaro, Bruna; Hermes-Pereira, Andressa; Schilling, Lucas Porcello; Fonseca, Rochele Paz; Kochhann, Renata; Hübner, Lilian Cristine (Dementia & neuropsychologia, 2020)
Verbal fluency (VF) has contributed to building cognitive maps as well as differentiating healthy populations from those with dementia. Objectives: To compare the performance of healthy controls and patients with mild cognitive impairment (MCI) and Alzheimer’s disease (AD) in two semantic VF tasks (animals/clothes) and a phonemic VF task (letter P). Also, to analyze the relationship between the frequency of reading and writing habits (FRWH) and VF in individuals with low educational level. Methods: Sixty-seven older adults aged 60-80 years and with 2-8 years of schooling were divided into three groups: controls (n=25), older adults with MCI (n=24), and older adults with AD (n=18). We analyzed the type, mean size, and number of clusters, switches, intersections, and returns. A post-hoc single-factor ANOVA analysis was conducted to verify differences between groups. Results: Total words in the phonemic VF and the animal category discriminated the three groups. Regarding the animal category, AD patients performed worse than controls in the total number of words, taxonomic clusters, returns, and number of words remembered. We found a moderate correlation between FRWH and total number of words in the phonemic fluency. Conclusions: Semantic (animate) and phonemic (total words) VF differentiated controls and clinical groups from each other - the phonemic component was more related to FRWH than the semantic one. The phonemic VF seems to be more related to cognitive reserve. VF tasks, considering total words and cluster analyses, are a valuable tool to test healthy and cognitively impaired older adults who have a low educational level. RESUMO. A tarefa de fluência verbal (FV) contribui para um mapeamento cognitivo e diferenciação entre populações saudáveis e com demência. Objetivos: Comparar o desempenho em duas tarefas de FV semântica (animais/roupas) e uma fonêmica (letra P) entre controles saudáveis e pacientes com Comprometimento Cognitivo Leve (CCL) e Doença de Alzheimer (DA). Além disso, analisar a relação entre frequência de hábitos de leitura e escrita (FHLE) e a FV nesses grupos de baixa escolaridade. Métodos: Sessenta e sete adultos idosos foram divididos em três grupos: controles (n=25), idosos com CCL (n=24) e idosos com DA (n=18), 60-80 anos de idade e 2-8 anos de escolaridade. Avaliaram-se tipo, tamanho médio e quantidade de agrupamentos, alternâncias, intersecções e retornos. Conduziu-se uma análise ANOVA de um fator com post hoc para verificar diferenças entre grupos. Resultados: O total de palavras na FV fonêmica e a categoria animais discriminaram os três grupos. Na categoria animais, pacientes com DA demonstraram desempenho inferior ao dos controles no número total de palavras, agrupamentos taxonômicos, retornos e número de palavras evocadas. Houve correlação moderada entre FHLE e número total de palavras na FV fonêmica. Conclusões: O componente semântico (animado) e o fonêmico (total de palavras) da FV diferenciaram os controles e os grupos clínicos entre si; o fonêmico relacionou-se mais com a FHLE do que o semântico. A FV fonêmica parece ser mais relacionada à reserva cognitiva. Tarefas de FV, considerando o total de palavras e as análises de clusters, são ferramentas valiosas para testar adultos idosos saudáveis e com declínio cognitivo na baixa escolaridade.